PENGARUH KOMUNIKASI PEMASARAN DAN SERVICE QUALITY TERHADAP BRAND AWARENESS PADA WISATA AIR TERJUN JANTUR DOYAM DI KABUPATEN BARITO UTARA - Irawati, Gina Sonia; Naparin, Muhammad; Indrayatie, Eko Rini (Jurnal Hutan Tropis, 2024)
North Barito Regency is known as one of the districts in Central Kalimantan Province with the capital being Muara Teweh. Jantur Doyam Waterfall is one of the leading tourist attractions in North Barito Regency which can be visited and is equipped with quite complete tourist facilities. However, this leading tourist attraction in North Barito Regency seems very empty of visitors because of the new tourist attractions which have created a desire to visit new places. Therefore, it is hoped that this research can show that effective marketing communications can help introduce tourism to visitors and good quality service can provide a satisfying experience, thereby creating top of mind Brand Awareness to increase the number of visits to the Jantur Doyam Waterfall tourist attraction. The purpose of this research is to determine the effect of marketing communications on brand awareness at Jantur Doyam Waterfall tourism and to determine the effect of service quality on brand awareness at Jantur Doyam Waterfall tourism. This research was carried out at Jantur Doyam Waterfall which is located in Mukut Village, Lahei District, North Barito Regency, Central Kalimantan Province. The method used in this research is a quantitative method using interviews and using the Smart-PLS 3 application. From the results of this research it was found that marketing communication variables have a significant effect on brand awareness and service quality also has a significant effect on brand awareness because it has a P-value less than   0, 05.